Ph.D Research in Economics - By Nepali Scholars at Home and Abroad - Shrestha, Mangala (Tribhuvan University Journal, 2010)
Not available. Key words: Economic problem in Nepal; Ph.D. Research Tribhuvan University Journal Volume XIV, 1991 Page: 43-48 Uploaded date: 5 October, 2010